Calibrating the factors of management quality in banking performance: a mixed method approach. Issue 3 (20th August 2018) - Chatterjee, Debmallya; Dhaigude, Amol S.
Abstract : Purpose: This paper aims to explore and model the factors of management quality dimension (FMQD) in evaluating banking performance. Design/methodology/approach: The FMQD in evaluating banking performance are explored through the review of literature. The identified factors are modeled using integrated fuzzy cognitive map (FCM) and Matrices' Impacts Croise's Multiplication Appliquée a UN Classement (MICMAC) approach. Scenario analysis is carried out on the proposed model to study the behavior in a dynamic setting. Findings: The main finding of this study is the prioritization of FMQD in evaluating banking performance. The cohesive model obtained by FCM-MICMAC integrated approach demonstrates that the interlinked factors can be grouped into independent, autonomous, dependent and relay clusters. The results suggest that internal control system is the most influential factor, whereas the business per employee is the most sensitive one in modeling management quality. Research limitations/implications: This study models the FMQD through expert opinions, and hence, individual bias may influence the results. This study can be further validated through statistical analysis. Practical implications: The study suggests that practitioners may focus more on these select factors and their mutual interactions to enhance management quality for improving the performance of the banks. The study emphasizes that better clarity and efficient designing of internal processes are the key to management soundness. Originality/value: This is the first study to explore and model FMQD in banking performance using FCM-MICMAC approach. Validation of the proposed model in a dynamic setting is also relatively new in the banking performance literature.